Antara Sungai dan Kota: Dinamika Permukiman Pesisir dan Delta di Lakkang Kota Makassar (1970-2013) - Fitra Widya Wati (Universitas Negeri Gorontalo, 2026)
This study aims to explain the social, economic, and cultural changes of the Lakkang community as a region living between the river environment and urban expansion. This study uses historical research methods through four stages: heuristics (collection of archival sources and interviews), source criticism (verification of the authenticity and credibility of data), interpretation (interpretation of cause-and-effect relationships), and historiography (writing analytical narratives). The results show that government decentralization and infrastructure development, such as electricity, docks, and clean water, have strengthened community connectivity with Makassar City. On the other hand, urbanization and river pollution pose new challenges to the sustainability of the traditional fishpond economy. The Lakkang community remains able to adapt by maintaining the values of siri' na pacce, kinship systems, and social solidarity as a local cultural identity that persists amidst the currents of modernity.